A study on the defensive stance and position of handball goalkeepers: facing a forward jump shot made from 9 meters - Yang, J. H.; Lee, Y. S. (Journal of Applied Biomechanics, 2016)
The purpose of this study was to find the defensive stance and calculate an optimal defense position for goalkeepers while blocking forward jump shots made from a distance of 9 m. Nine men`s handball matches were recorded and 78 video clips were selected for analysis. These are the top class goalkeepers, which included players from the national team and reserve team of Korea. The goalkeeper`s actual defensive position was significantly different from instructional suggestions; the width of both feet of the goalkeeper was approximately 2.5 times the width of the shoulders, and the hands were at waist height. The goalkeeper`s actual defense position was about 1.10 (± 0.3) m from the goal line and also significantly different than instructional material (0.75 m). The optimal defense position, which was calculated from the goalkeeper`s actual movement, was 1.44 m from the goal line, because the ratio of goalkeeper`s defensive area in relation to the total area to be defended is highest at this point. In summary, we recommended that handball goalkeepers move forward, about a half step (0.34 m), when defending a forward jump shot made from 9 m, and instructional material should be modified according to the findings from this study.